2003
DOI: 10.1177/0890334403255344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Lactation Support Service in a Children's Hospital Neonatal Intensive Care Unit

Abstract: Breastfeeding hospitalized infants can be difficult. The authors assessed the effectiveness of an International Board Certified Lactation Consultants (IBCLC) service to increase the proportion of infants given their own mother's milk (OMM) in a children's hospital neonatal intensive care unit (NICU). The charts of 350 randomly selected patients admitted the year before and after implementation of the service in July 1997 were abstracted. Factors significantly associated with infants being given OMM included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 36 publications
(45 reference statements)
2
49
0
1
Order By: Relevance
“…These findings suggest the importance of supporting mothers during the stress of having a baby admitted to the NICU and are consistent with previous studies, which also found mothers benefit from programs, including lactation support in the NICU setting. 4,5,7,8,[10][11][12]15,16 In comparing rates of infants receiving any HM in the IB versus OB subgroups, the IBCLC greatest impact was seen in the OB subgroup during NICU hospitalization and at discharge. We feel that the rates of IB infants receiving any HM in our study population had already been maximized, and thus the addition of an IBCLC had little impact on the IB subgroup.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These findings suggest the importance of supporting mothers during the stress of having a baby admitted to the NICU and are consistent with previous studies, which also found mothers benefit from programs, including lactation support in the NICU setting. 4,5,7,8,[10][11][12]15,16 In comparing rates of infants receiving any HM in the IB versus OB subgroups, the IBCLC greatest impact was seen in the OB subgroup during NICU hospitalization and at discharge. We feel that the rates of IB infants receiving any HM in our study population had already been maximized, and thus the addition of an IBCLC had little impact on the IB subgroup.…”
Section: Discussionmentioning
confidence: 94%
“…They reported 71% of the mothers were breast-feeding at the time of their infant's discharge from the NICU; no preintervention rates were reported. Gonzalez et al 12 reported a significant increase in the proportion of babies receiving HM from 31 to 47% (P ¼ 0.002), while they were in the NICU following the implementation of a comprehensive International Board Certified Lactation Consultant (IBCLC) service, including a telephone helpline and LC presence. At discharge the percentage of infants receiving HM increased from 23 to 37% (P ¼ 0.004).…”
Section: Introductionmentioning
confidence: 97%
“…The majority work in outpatient settings (Centers for Disease Control and Prevention, 2014; Thurman and Allen, 2008). Improved initiation and duration rates of breastfeeding have been demonstrated in neonatal intensive care units with dedicated lactation consultant services (Castrucci et al, 2007; Gonzalez et al, 2003; Pinelli et al, 2001; Wambach et al, 2005). However, lactation consultants are not routinely available in neonatal intensive care units and it is unclear whether they complement or substitute for nursing care that is provided around the clock (Hallowell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…9 Some studies describe programs to promote breastfeeding among mothers of preterm infants. 10 They stress the importance of providing support to mothers by qualified professionals, [11][12][13][14] and the benefits of support offered by the community and the family. [15][16][17][18] The purpose of this study was to describe a breastfeeding intervention to provide support and information to mothers of preterm newborns and to evaluate its effects on breastfeeding rates in the first 6 months after hospital discharge.…”
Section: Introductionmentioning
confidence: 99%